2017
DOI: 10.1093/eurheartj/ehx026
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and clinical outcome of uptitration of ACE-inhibitors and beta-blockers in patients with heart failure: a prospective European study

Abstract: Patients with HFrEF who were treated with less than 50% of recommended dose of ACE-inhibitors/ARBs and beta-blockers seemed to have a greater risk of death and/or heart failure hospitalization compared with patients reaching ≥100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
329
3
31

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(381 citation statements)
references
References 52 publications
18
329
3
31
Order By: Relevance
“…5 In particular, combination therapy with renin-angiotensinaldosterone system inhibitor (RAASi) and/or mineralocorticoid receptor antagonist (MRA) agents, while recommended to reduce the incidence of hospitalization, 5 may further increase the risk of hyperkalaemia in this already-vulnerable population. [8][9][10] At present, the clinical burden of hypokalaemia and hyperkalaemia among European HF patients, and relationships between serum potassium and adverse clinical outcomes in this population, is not well characterized. [8][9][10] At present, the clinical burden of hypokalaemia and hyperkalaemia among European HF patients, and relationships between serum potassium and adverse clinical outcomes in this population, is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…5 In particular, combination therapy with renin-angiotensinaldosterone system inhibitor (RAASi) and/or mineralocorticoid receptor antagonist (MRA) agents, while recommended to reduce the incidence of hospitalization, 5 may further increase the risk of hyperkalaemia in this already-vulnerable population. [8][9][10] At present, the clinical burden of hypokalaemia and hyperkalaemia among European HF patients, and relationships between serum potassium and adverse clinical outcomes in this population, is not well characterized. [8][9][10] At present, the clinical burden of hypokalaemia and hyperkalaemia among European HF patients, and relationships between serum potassium and adverse clinical outcomes in this population, is not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…β-blockers and AngII receptor inhibitors have become widely used and effective cardiovascular medicines (Liao et al, 2004; Ouwerkerk et al, 2017). In the present study, we found that LPA 3 deficiency led to reduced cardiac function and increased infarct size after MI.…”
Section: Discussionmentioning
confidence: 99%
“…14 In BIOSTAT-CHF, patients receiving >50 % of recommended doses of ACEIs and BBs had better outcomes than those taking lower doses. 14 Similarly, in the Austrian Heart Failure Registry, improved guideline adherence related to dose escalation towards optimal levels was associated with reduced long-term mortality in ambulatory HFrEF patients surviving 1 year after registration. 15 …”
Section: Clinical Practicementioning
confidence: 91%